Life Events, Parenting, and Delinquency: Assessing the Interactive Effects and Gender Differences among Chinese Adolescents - Liu, Ruth X. (International criminal justice review, 2025)
This study integrates several research lines to assess whether and how harsh and warm parenting behaviors may each modify the relationship between adverse life events and delinquent adaptations among Chinese adolescents. Furthermore, this study assesses whether the hypothesized moderating effects may vary among male and female adolescents. Data drawn from over 500 middle school students from an urban city in China yield results quite consistent with the expectations. Exposure to adverse life events and harsh parental discipline are independently associated with elevated levels of delinquent participation, and these relationships are observed among both male and female adolescents. Furthermore, the effects of stressful life events on delinquency depend upon levels of parental behaviors as well as the gender of adolescents. Specifically, harsh parental discipline in conjunction with stressful life events is related to higher levels of delinquency among Chinese female adolescents, whereas warm parenting offsets the effect of adverse life events on delinquency among male adolescents. These results are discussed in term of their theoretical importance and cultural implications.